ANALYSIS OF CONSUMER PURCHASING DECISIONS ON E- COMMERCE PLATFORMS - Loso Judijanto; Tamrin Lanori; Nirwan Mulyatno (Adisam Publisher, 2024)
This literature research aims to analyze the factors that influence consumer purchasing decisions on e-commerce platforms. This research identifies and evaluates internal and external factors that contribute to the consumer decision-making process. Internal factors include personal needs and preferences, previous experiences, and consumer demographic conditions, while external factors include the quality of user experience, platform reputation and security, marketing strategies, and social influence from family, friends, and social media. Data was collected through surveys and in-depth interviews with e-commerce consumers to gain comprehensive insights. The research results show that consumer purchasing decisions are strongly influenced by a combination of these factors. The quality and ease of use of the platform, transaction security, and effective promotions play a significant role in driving purchasing decisions. Additionally, social influence and reviews from other users are also cited as important factors in shaping consumer perceptions and trust in the platform. In conclusion, e-commerce platforms must focus on improving user experience, ensuring the security and reliability of transactions, and implementing targeted marketing strategies to attract and retain consumers. By understanding and managing these factors effectively, e- commerce platforms can increase consumer loyalty and achieve long- term business success.